Telocytes: current methods of research, challenges and future perspectives - Sanches, Bruno D. A.; Teófilo, Francisco B. S.; Brunet, Mathieu Y.; Villapun, Victor M.; Man, Kenny; Rocha, Lara C. [UNESP]; Neto, Jurandyr Pimentel [UNESP]; Matsumoto, Marta R.; Maldarine, Juliana S.; Ciena, Adriano P. [UNESP]; Cox, Sophie C.; Carvalho, Hernandes F. (Springer Nature, 2024)
Telocytes (TCs) are CD34-positive interstitial cells that have long cytoplasmic projections, called telopodes; they have been identified in several organs and in various species. These cells establish a complex communication network between different stromal and epithelial cell types, and there is growing evidence that they play a key role in physiology and pathology. In many tissues, TC network impairment has been implicated in the onset and progression of pathological conditions, which makes the study of TCs of great interest for the development of novel therapies. In this review, we summarise the main methods involved in the characterisation of these cells as well as their inherent difficulties and then discuss the functional assays that are used to uncover the role of TCs in normal and pathological conditions, from the most traditional to the most recent. Furthermore, we provide future perspectives in the study of TCs, especially regarding the establishment of more precise markers, commercial lineages and means for drug delivery and genetic editing that directly target TCs.
Keywords: Immunomarkers; Methods; Single-cell RNAseq; Telocytes; Ultrastructure